An updated 1-dimensional seismic velocity model has been developed for the Mw 6.1 Pasaman earthquake that occurred on February 25, 2022 - Sihotang, Bertalina; Humaidi, Syahrul; Simanjuntak, Andrean V. H. (Politeknik Negeri Batam, 2024)
On February 25, 2022, a strong-felt earthquake with magnitude Mw 6.1 occured within the western portion of Pasaman, West Sumatra, Indonesia. The impact of the seismic activities has produced an enormous shaking which measured as VI on the Adjusted Mercalli Concentrated (MMI) and II -III MMI until Malaysian and Singapore region. The casualty's reports contain the data approximately the broadly harms such as, 1765 residences and murdered at slightest 18 individuals in West Sumatra Area. A dependable dynamic blame was already unidentified and raise a major address almost the association with Sumatra dynamic blame. Therefore, this analysis examines the attributes of seismic activity and the damage caused by utilizing an appropriate 1-Dimensional seismic velocity model. The acquired 1-Dimensional speed data exhibits varying values at a depth of 10 km with a velocity of approximately 5.5 km/s and at 30 km with a velocity of approximately 7 km/s. The 1-D velocity obtained exhibits a parallel and distinctive pattern with an RMS value of less than 1.0. In addition, the PGA records reveal a seismic intensity of 10% in Pasaman, consistent with the damage reports obtained during field assessments. This indicates that Pasaman is located in a zone with frequent seismic activity.